Women’s resilience in Fiji: how laws and policies promote gender equality in climate change and disaster risk management (Asian Development Bank)
Globally, women are disproportionately impacted by climate change and disasters due to gender inequalities and limited opportunities to participate in decision-making processes. Addressing this imbalance requires the integration of gender equality in laws and policies on climate change and disaster risk management, as well as ensuring gender equality are key outcomes in building social and economic resilience. This report presents findings of a gender analysis of national legal and policy frameworks of Fiji and discusses whether laws, policies, and strategies consider gender inequalities as they relate to climate and disaster risk management. The report includes a set of specific and general recommendations to address some of the gaps in laws and policies that affect women’s resilience to climate change and disasters in Fiji.